The Impact of Emotional Intelligence on Administrative Leadership Characteristics - Xu, Jinliang; Rafols, Jaruvic (Journal of Interdisciplinary Perspectives, 2025)
This research investigated administrators' leadership characteristics and emotional intelligence within Chengdu Road and Bridge Construction of CDCEG, Chengdu, China. The study was undertaken by surveying 121 administrators using the Multifactor Leadership Questionnaire (MLQ) and the Bar-On Emotional Quotient Inventory (BarOn EQ-S). Descriptive–comparative–-correlational design with statistical data indicated that the organizational workforce is male-dominated, with a significant proportion of the sample being young. The leadership styles were mainly transformational and transactional, with average passive levels of leadership. Notable differences in interpersonal emotional intelligence have been identified based on gender and years of professional experience; however, no significant differences in demographic profiles concerning leadership traits were seen. In the case of leadership characteristics and emotional intelligence, there were weak and nonsignificant correlations. The study concluded that emotional intelligence is not a prime determinant of leadership behavior among administrators, suggesting a multivariable perspective for developing leadership. Recommendations extend to workforce diversity, balancing leadership styles, enhancing emotional intelligence through targeted development, and taking comprehensive approaches to leadership training. This study has valuable insights into best leadership practices within the engineering and design sector, relevant to any cultural and industrial context with similar features.